2012
DOI: 10.15282/jmes.2.2012.10.0021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fuel Temperature on a Diesel Engine Performance Operating with Biodiesel Blended

Abstract: This paper presents the study of the effect of temperature on diesel engine performance using a 5% biodiesel blend. A one-dimensional numerical analysis is used to simulate the four-cylinder diesel engine. The diesel engine simulation is used to study the characteristics of engine performance when the engine is operating with a fuel blend as an alternative fuel. The simulations are conducted at full load conditions where the temperature varies from 300 to 500 K. The results show that the maximum brake power an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…For example, a fuel that has 20% biodiesel will be denoted by B20. When comparing biodiesel to petroleum-based diesel fuel, it is clearly evident that biodiesel is a lot more environmentally friendly [17][18][19][20][21][22]. A study sponsored by the United States Department of Agriculture and Department of Energy revealed that "Biodiesel yields 3.2 units of fuel product energy for every unit of fossil energy consumed in its life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a fuel that has 20% biodiesel will be denoted by B20. When comparing biodiesel to petroleum-based diesel fuel, it is clearly evident that biodiesel is a lot more environmentally friendly [17][18][19][20][21][22]. A study sponsored by the United States Department of Agriculture and Department of Energy revealed that "Biodiesel yields 3.2 units of fuel product energy for every unit of fossil energy consumed in its life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the differences between diesel and biodiesel fuels, the optimum parameter of diesel engines may not seem suitable for biodiesel. Engine conditions should thus be modified based on the fuel or fuel blends to achieve optimum performance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced radical formation extends the lean combustion limit (Caillo, Delorme, Denis, Berardi, & Porterie, 2002;El-Sherif, 1998). In premixed-charge spark-ignition engines, ethane addition increases the flame propagation rate (Rahim, Mamat, Taib, & Abdullah, 2012;Yossefi et al, 2000). No significant effects on CO emissions are reported in most engine studies; however, some researchers report increases in HC emissions with increased ethane and propane concentrations (Bhaskar, Nagarajan, & Sampath, 2010;Min, Bang, Kim, Chung, & Park, 1998), although these results are not consistent across all reported studies.…”
Section: Introductionmentioning
confidence: 92%